2012
DOI: 10.1186/1472-6939-13-11
|View full text |Cite
|
Sign up to set email alerts
|

One and done? Equality of opportunity and repeated access to scarce, indivisible medical resources

Abstract: BackgroundExisting ethical guidelines recommend that, all else equal, past receipt of a medical resource (e.g. a scarce organ) should not be considered in current allocation decisions (e.g. a repeat transplantation).DiscussionOne stated reason for this ethical consensus is that formal theories of ethics and justice do not persuasively accept or reject repeated access to the same medical resources. Another is that restricting attention to past receipt of a particular medical resource seems arbitrary: why couldn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…8 The reality is not as clear, however, as society preferences for fairness in accessing indivisible healthcare resources must also be considered. 20 There needs to be further consideration going forward on how to allocate organs when outcomes are comparable for retransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…8 The reality is not as clear, however, as society preferences for fairness in accessing indivisible healthcare resources must also be considered. 20 There needs to be further consideration going forward on how to allocate organs when outcomes are comparable for retransplantation.…”
Section: Discussionmentioning
confidence: 99%
“…12 Others have argued that prior transplantation should be considered when allocating donor organs to reduce the frequency of some recipients receiving multiple transplants while others die waiting for organs. 13 Prognostic models have indicated that the need for life support, use of split liver grafts, neonatal or familial cholestasis, paucity of bile ducts, and congenital abnormalities are associated with poor outcomes for children after liver retransplantation. 14 Split liver grafting was first used in children in Australia and New Zealand in 1989 to maximise the number of patients receiving transplants, 15 and since 2002 optimal donor livers have been split whenever possible.…”
mentioning
confidence: 99%
“…Some ethicists have proposed that potential recipients be prioritised exclusively according to urgency and the likelihood of 5‐year survival 12. Others have argued that prior transplantation should be considered when allocating donor organs to reduce the frequency of some recipients receiving multiple transplants while others die waiting for organs 13…”
mentioning
confidence: 99%
“…Similar consideration was discussed concerning the care of obese patients and re-transplantation in subjects who had lost a previous graft due to non-adherence to treatments [91][92][93][94][95][96].…”
Section: Discussionmentioning
confidence: 99%